Supporting Factors in Implementing Joint Analysis Policy between the Directorate General of Tax and Customs and Excise - Wandayani Nurfadilah; Haula Rosdiana (Jurnal Administrasi Publik (Public Administration Journal), 2020)
The Ministry of Finance released the Synergy Program (Joint Program) in 2017, where one of the subprograms is a Joint Analysis between the Directorate General of Tax and Customs. Joint Analysis is intended to optimize state revenue, tax compliance and can be developed by other subprograms. The implementation of Joint Analysis can encompass non-compliant importers and exporters and close the tax avoidance gap by shifting the location of activities or company domiciles between regions of Indonesia. The purpose of this study is to analyze the enabling factors in implementing a joint analysis policy between the Directorate General of Tax and Customs. This study adopts the positivism paradigm with qualitative methods. Primary data sources were obtained through in-depth interviews with selected informants. The results showed that political support and commitment from the leadership were quite good, but equal treatment at the Regional Office level was still a chore to complete. The legal regulations are complete and clear enough to accommodate the implementation of the program even though the technical operational standards at the Regional Office level are not yet rigid. Resources and governance are quite good although it requires time for the joint team to learn about business processes. Understanding between parties is considered quite good with the growing development of trust and joint commitment to secure state revenue. Communication between joint teams is done practically and flexibly, data exchange can be by email or WhatsApp group. The use of data analytics applications is also quite effective even though it has not yet reached all Regional Offices.